Correction: Catalytic hydrogenolysis of kraft lignin to monomers at high yield in alkaline water. Issue 17 (14th August 2017) - Qi, Shi-Chao; Hayashi, Jun-ichiro; Kudo, Shinji; Zhang, Lu
Abstract : Correction for 'Catalytic hydrogenolysis of kraft lignin to monomers at high yield in alkaline water' by Shi-Chao Qi et al., Green Chem., 2017, 19, 2636–2645.